Perlindungan Konsumen terhadap Klausula Eksonerasi Perjanjian Baku Pengiriman Barang pada JNT di Kota Kupang - Stevania Caroline Prata; Darius Mauritsius; Helsina F. Pello (Pusat Riset dan Inovasi Nasional, 2025)
The standard agreement for the delivery of goods whose contents or clauses are made by business actors to avoid losses on another day and consumers only have the choice to accept or reject, thus making the position of business actors stronger while consumers are weakened. The UUPK itself does not prohibit the existence of an exoneration clause as long as it does not violate article 18 of the UUPK. The type of research is field research or Empirical Juridical research is carried out by starting from primary data obtained from the research site, the data collection technique is through literature studies and analyzed in a qualitative way, which is a discussion that is carried out by combining literature research and field research. The results of the research obtained in the study show that consumers have been protected by Law No. 8 of 1999 concerning Consumer Protection, If a dispute occurs and a family settlement has been carried out but there is no result or no peace occurs, then consumers can take legal action as stipulated in articles 24 and 25 of the UUPK regarding how the responsibility of business actors, in the resolution of consumer disputes is protected by article 45 of the UUPK concerning dispute resolution. Dispute resolution can be done through the court and out of court, out-of-court dispute resolution can be done by filing a claim for compensation or through the consumer dispute resolution agency (BPSK). As a legal consequence that occurs if there is a clause in the standard agreement that is null and void, even though the standard agreement containing an exoneration clause has been agreed before, the agreement cannot be considered valid because it contradicts one of the contents of article 1320, which is a halal cause, due to the transfer of responsibility.